Genomic and chromosomal organization of Ty1- copia-like sequences in Olea europaea and evolutionary relationships of Olea retroelements - Stergiou, G.; Katsiotis, Andreas; Hagidimitriou, M.; Loukas, M. (My University, 2002)
The Ty1- copia-like retrotransposon is one of the commonest class of transposable elements in the plant kingdom, often comprising several percent of the total DNA content. We aimed to study the evolutionary relationships of Olea retroelements, using part of the reverse transcriptase domain, as well as the genomic and chromosomal organization of these sequences in Olea europaea chromosomes and their transcription activity and copy number. Fourteen clones, that were isolated from four different species, were sequenced and a phylogenetic tree was constructed based on their predicted amino acids. Five clones derived from O. europaea were clustered together with a 87% nucleotide sequence homology and two Olea oleaster clones showed 98% sequence homology. The rest of the clones showed heterogeneity among them, leading to a common ancestral transposon that existed before the genus arose. The Ty1- copia-like sequences have a dispersed genomic organization, physically distributed on all chromosomes, showing minor clustering in some cases and low copy numbers in the smallest chromosome pair. The total copy number in the O. europaea genome was estimated by dot blotting to be 40,000 in a haploid nucleus, but a number of these are non-functional since the sequenced clones contained stop codons and frame-shifts. Some Ty1- copia-like copies, present in O. europaea, were found to be methylated, while no differences in methylation were observed between DNA isolated from young leaves and callus-suspension cultures.
Keywords: Evolution; Methylation; Molecular cytogenetics; Olive; Reverse transcriptase